The Role of Teachers' Teaching Styles in Improving Mathematics Learning Motivation in Elementary Schools - Pratiwi, Dian Anggi; Musonda, Allan; Zawita, Honer N. (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The aim of the research is to determine the influence of teacher teaching style on students' motivation to learn mathematics. Methodology: This research was conducted at 166 Turucinnae State Elementary School, Bone Regency, with 60% of the 100 students as samples, while data collection used a questionnaire technique, namely a closed questionnaire. In this study, descriptive analysis and inferential analysis were used. Main Findings: The results of the data analysis show that the teacher's teaching style (X) has a significant influence on learning motivation (Y) which is indicated by the correlation coefficient value of obtained at a significance level of 5%. In this case, H1 is accepted and Ho is rejected. From these results, it is proven that there is an influence of the teacher's teaching style on the motivation to learn Mathematics of students at State Elementary School 166 Turucinnae, Bone Regency. Novelty/Originality of this study: The results of this study offer an innovative approach for teachers to adapt a more effective teaching style in encouraging students' interest and enthusiasm for learning mathematics in the primary education sector.